Facile modification using organic acid molecules to neutralize residual alkaline compounds for stabilizing LiNi0.95Co0.04Mn0.01O2 cathode material - Chao Zhao; Xiangshao Yin; Yuanyuan Huang; Xinyu Zhang; Weihong Jiang; Zhuo Zhou; Wenhui Tu; Xianshu Wang; Ding Wang; Jianguo Duan (Energy Materials and Devices)
The presence of residual alkaline compounds in the ultrahigh-nickel layered oxide cathodes (LiNixCoyMn1−x−yO2, x ≥ 0.9) aggravates structural degradation, increases surface reactivity, and promotes slurry gelation, leading to the capacity decay of batteries with these cathodes and complicating their manufacturing. Traditional approaches for addressing this issue, including direct removal, coverage, and utilization, are complex and require surface regeneration. Herein, we propose neutralizing residual alkaline compounds with 3-thiopheneboronic acid (3-TBA) to improve the performance of LiNi0.95Co0.04Mn0.01O2 (NCM) cathode material, a facile strategy that does not require any post-treatment. The suggested reaction yields a uniform and thin organic-modified layer on the surface of the NCM cathode, improving its chemical stability toward the electrolyte, as demonstrated by multiple characterization methods. The modified NCM cathode exhibited impressive cyclic and rate performances, achieving a capacity retention of 83.34% after 200 cycles at 1.0 C and a specific capacity of 162.00 mAh·g−1 at 10.0 C. Most importantly, the proposed approach can efficiently suppress unfavorable phase transitions, severe electrolyte degradation, and CO2 gas evolution, improving the application potential of ultrahigh-nickel layered oxide cathode materials.